Wind waves in a flume - Chin, Hok-leong; Shuto, Nobuo; Ackermann, Norbert L.; Hudson, Norman W.; New Zealand Government (Bangkok, Thailand : Asian Institute of Technology, 1973)
This paper describes the experimental study of wind-waves in a flume. The experiment shows that the shear stress supplied by the wind is principally distributed to shear stresses required to produce wave, to induce water current and to support water slope. The shear stress required to produce wave is the dominant shear stress in the energy transfer from winds to water and is about 90% of the wind shear stress. Waves grow linearly at the initial fetch and then follow the exponential growth which has the same tendency of the combined theory given by Miles. The power of the energy spectrum curve for higher frequency in the neigh bourhood of the primary peak depends on fetch. The water surface current increases with fetch. The roughness of the water surface depends on fetch and approaches significant wave height at the downstream. At the initial fetch, the water surface can be regarded as smooth. The roughness and the friction coefficient in the present experiment are always smaller than that obtained from fully developed sea. The charnock expression is not constant. Winds over smooth plate in the flume is also investigated, which shows that the turbulent inner layer thickness can be expressed by the exponential function of the fetch and the entrance velocity. The outer boundary layer thickness almost grows linearly with the fetch. The wind shear stress over smooth plate is always smaller than that over water surface except at the initial fetch.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand .
Thesis (M.Eng.) - Asian Institute of Technology, 1973
Keywords: Flumes; Wave mechanics